ANALISIS DATA PENERIMAAN SINYAL ADS-B DALAM MENENTUKAN LOKASI PESAWAT MENGGUNAKAN RTL-SDR DAN LOW NOISE AMPLIFIER - Adam Bintang Defino; Popy Maria; Sahid Ridho; Ummul Khair (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
Automatic Dependent Surveillance-Broadcast (ADS-B) allows real-time monitoring of aircraft positions, but Software Defined Radio (SDR) devices such as the RTL-SDR have sensitivity limitations that can affect signal reception quality, especially at long distances or under less than ideal conditions. This study designs an ADS-B receiver system based on the RTL-SDR equipped with a Low Noise Amplifier (LNA) to amplify weak signals without adding significant noise. The method includes receiver circuit design, antenna installation, LNA integration, and signal reception testing at various distances. Reception data with and without the LNA are compared based on the maximum distance and the number of messages received. The results show that the LNA increases the maximum reception distance from 309.95 km to 417.90 km and improves signal stability at medium and short distances. This system is able to capture more messages, including from aircraft under less than ideal propagation conditions. The combination of the RTL-SDR and LNA has proven to be effective and economical as an alternative to expensive device-based flight monitoring.